Competitiveness and economic development scenarios of Latvia - Auzina-Emsina, Astra; Ozolina, Velga; Pocs, Remigijs (Business, Management and Economics Engineering, 2018)
The paper deals with the analysis of exports and competitiveness in Latvia in comparison with Estonia and Lithuania. The objective of the study is to elaborate the possible sectoral development scenarios based on the competitiveness analysis results. The main focus is on exports of goods and revealed comparative advantage (RCA) of exported products as compared to the EU exports. Scenarios are elaborated to model economic development by industries using Latvian Model of Development (LMD), which is a macro-econometric model. Results argue that the economic development is higher, if the competitiveness ensures both higher export growth and import substitution. RCA is an appropriate method to apply in competitiveness studies and the research findings can be used in economic policy and analysis.